2017
DOI: 10.5812/aacc.62239
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Satisfaction of Spinal Anesthesia for Elective Cesarean Section in an Academic Hospital

Abstract: Background: Currently, spinal anesthesia is an acceptable method for cesarean section (CS) throughout the world, since general anesthesia is associated with higher maternal morbidity and mortality rates. The current study was performed to survey different factors for maternal satisfaction of spinal anesthesia. Methods: This cross sectional study was performed on women who were candidates for elective CS at Dr. Shariati hospital. Informed consents were obtained from all the patients, and the risks and side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In the current study, even if needle prick pain had a higher frequency (191 (49.9%)), it is not significantly associated with maternal satisfaction. Our finding was parallel with the other study which showed that needle prick pain was not significantly associated with the level of maternal satisfaction [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the current study, even if needle prick pain had a higher frequency (191 (49.9%)), it is not significantly associated with maternal satisfaction. Our finding was parallel with the other study which showed that needle prick pain was not significantly associated with the level of maternal satisfaction [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our result was similar to a study done by Sadaghi M and his colleagues regarding maternal satisfaction of spinal anesthesia for elective cesarean section which showed that 83.8% of parturients were satisfied. Additionally, 78.5% parturients showed willingness to choose spinal anesthesia in the future surgeries [ 4 ]. Another study done by Rashad Siddiqi and Syed Asadullah revealed that the overall level of satisfaction among the parturients who underwent cesarean delivery under spinal anesthesia was 81.4% and 53.66% who would opt for spinal anesthesia in the future [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ellakany [24] provided that patients received thoracic spinal anesthesia had better satisfaction than patients received general anesthesia with no significant difference between both groups in PONV, but surgeon satisfaction was higher for GA group than thoracic SA group. Also, studies done by (Acikel et al, and Mostafa et al, [25,26] provide higher patients satisfaction with spinal anesthesia.…”
Section: Discussionmentioning
confidence: 98%